RANCANG BANGUN MESIN PUNTIR UNTUK PEMBUAT BESI TERALIS MODEL SPIRAL SPESIFIKASI BESI KOTAK 10X10X1000 mm - Dicky Kurniawan; Safril Safril; Bukhari Bukhari (Politeknik Negeri Padang, 2018)
Today the need for housing (home) is increasing. Touch of beauty and support in terms of security are widely used in the construction of the house, one of the trellis. One of the production processes in processing iron trellis is the process of forming spiral iron trellis models of a certain size, in the process special machines are needed that can alleviate, simplify, and accelerate human work. This process is also called cold work because without the heat treatment process. The specifications of the trellis iron torsion machine are 1500x500x800 mm. This machine has several driving units, namely: Motor as a driver, and reducer to reduce the rotation of the shaft on the swivel chuck, and use belt transmission and chains. From the calculation and design of the engine, the motor power of ½ Hp is obtained, the production capacity is 10x10x1000 mm, the shaft diameter is 25.4 mm. The production time of this machine is 7 times / workpiece or ± 2 minutes / Pcs or 29 to 30 Pcs / hour. This trellis iron torsion machine works well and gets a better and stronger spiral model iron box. The components contained in this machine include: Electric motors, pulleys, belts, frames, sprocket, chains, chucks, bearings and speed reducers.